Gender Inequality in Education in Nagekeo Regency, East Nusa Tenggara - Resti Ayu, Agnes (Iapa Proceedings Conference, 2025)
Gender inequality in education remains a persistent development issue across Indonesia, particularly in the eastern regions such as Nagekeo Regency, East Nusa Tenggara (NTT). This paper examines how cultural, structural, and policy-related factors interact to shape unequal access, participation, and outcomes between male and female students. Using a qualitative descriptive approach through document analysis of government reports, statistical data, and academic publications, the study identifies that early marriage, heavy domestic workloads, and patriarchal norms significantly restrict educational participation among girls. Despite the presence of national and regional gender mainstreaming policies, their implementation in Nagekeo has not yet achieved transformative results. The findings highlight that gender inequality in education is not merely an issue of access but also of power relations and social structures that continue to reproduce disparities. The study concludes that integrating gender-responsive budgeting, community awareness campaigns, and capacity building for local governments is essential to promote inclusive education and sustainable human development in eastern Indonesia.